Consumer Evaluation of the Degree of Doneness of Beef Strip Loin Steaks Cooked to Six End-Point Temperatures - L. L. Prill; L. N. Drey; J. L. Vipham; M. D. Chao; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:The objective of this study was to assess consumers’ degree of doneness practices in addition to their ability to identify beef steak degrees of doneness. Study Description:Beef strip loins (n = 24) from 12 animals representing five quality treatments [Prime, Top Choice, Low Choice, Select, and Select Enhanced (108%)] were collected. Steaks were cooked to an end-point temperature of very-rare (130°F), rare (140°F), medium-rare (145°F), medium (160°F), well-done (170°F), or very well-done (180°F). Cooked steaks were cut in half, perpendicular to the long axis of the steak, and photographs were taken immediately on the internal face of the lateral side. A digital survey for consumers was developed for electronic evaluation of the cooked steak images. Consumers (n = 1,134) answered a demographics questionnaire, followed by questions pertaining to temperature and determining degree of doneness. Next, 10 steak images depicting varying degrees of doneness were randomly selected by Qualtrics Software for each consumer to identify the degree of doneness of the steak pictured. The Bottom Line:Consumers do not have a good understanding of beef degrees of doneness, and are unable to consistently and accurately identify degrees of doneness of steaks cooked to specified end-point temperatures. This can create challenges when consumers communicate their degree of doneness preferences at foodservice establishments.
Keywords: consumer; degree of doneness; temperature